2007
DOI: 10.1016/j.otohns.2006.11.057
|View full text |Cite
|
Sign up to set email alerts
|

Sublingual Immunotherapy: Past, present, paradigm for the future?A review of the literature

Abstract: Since the early 1900s, allergen immunotherapy has been recognized as an effective treatment option for patients with inhalant allergies. Subcutaneous injection has traditionally been the main route of antigen delivery for immunotherapy in the United States. Over the past 15 years, sublingual administration of allergen extract has become a widely used method of immunotherapy in other countries, particularly in Europe. Although sublingual immunotherapy (SLIT) has been used by some physicians in the United States… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 140 publications
0
33
0
Order By: Relevance
“…4,8,[13][14][15] To date, there are many publications regarding the clinical efficacy of SLIT, although very few consider laboratory analyses of SLIT action. [16][17][18][19][20] Most of these concern the evaluation of inflammatory mediators and cytokine concentrations in bronchoalveolar lavage fluid and in serum obtained from asthmatic subjects treated with SLIT. 13,[17][18][19] The influence of SLIT on basophil surface antigens as activation markers is limited.…”
Section: Introductionmentioning
confidence: 99%
“…4,8,[13][14][15] To date, there are many publications regarding the clinical efficacy of SLIT, although very few consider laboratory analyses of SLIT action. [16][17][18][19][20] Most of these concern the evaluation of inflammatory mediators and cytokine concentrations in bronchoalveolar lavage fluid and in serum obtained from asthmatic subjects treated with SLIT. 13,[17][18][19] The influence of SLIT on basophil surface antigens as activation markers is limited.…”
Section: Introductionmentioning
confidence: 99%
“…The s.l. route is also effective and efficient for allergen-specific immunotherapy (7,8). Recently, we demonstrated that s.l.…”
mentioning
confidence: 99%
“…Tolerance occurs as a result of an increase from a specific allergen suppressor T cell, and Treg after immunotherapy [33]. A new perspective of the therapeutic approach focuses on administering IL-2 to inflamed tissue in autoimmune and allergic-induced inflammatory cases.…”
Section: Discussionmentioning
confidence: 99%